ADAPTIVE LEADERSHIP DECISION-MAKING UNDER UNCERTAINTY: A SOCIAL-PSYCHOLOGICAL PERSPECTIVE (Scientific Conference on Multidisciplinary Studies, 2025)
Uncertainty, complexity, and rapid change increasingly define today’s higher education landscape. This paper examines adaptive leadership as a psychological framework that enables effective decision-making under uncertain and ambiguous conditions. Drawing on theories of groupthink (Janis, 1972), reflective thinking, and emotional resilience, the study evaluates how tolerance for ambiguity and social influence shape leaders’ choices. Data were collected from 120 university managers in Uzbekistan using scenario-based experiments and interviews. Findings reveal that leaders with high ambiguity tolerance, openness to feedback, and reflective capacities adapt more effectively to uncertainty. The research contributes to understanding how social-psychological mechanisms can improve adaptive decision-making and institutional innovation in higher education management.